Surgical treatment of parathyroid cysts: case series and review of literature - Odalović, Božidar; Buzejić, Matija; Zorić, Goran; Rovčanin, Branislav; Živaljević, Vladan; Cvetković, Saša; Husović, Damir; Paunović, Ivan (Vojnosanitetski pregled, 2023)
Introduction. Parathyroid cysts (PCs) are divided into two categories: functional and nonfunctional. If large enough, both types of PCs can present as a mediastinal or cervical mass in 1–5% of patients. Case report. A retrospective analysis of the data on patients operated on for primary hyperparathyroidism or cervical/mediastinal mass from 2016 to 2021 was conducted. An analysis of the demographic data of the patients, data on preoperative fine needle aspiration biopsy, level of parathyroid hormone in serum pre- and postoperatively, level of serum calcium, as well as on clinical presentation of the disease, was carried out. In this five-year period, a total of 555 patients were operated on, in whom the parathyroid gland was described as a definitive pathohistological finding. Of the total number, PCs were found in seven cases. In five out of the seven cases, PC was nonfunctional. Four female and three male patients were operated on due to PC. The mean age of operated patients was 49.8 years. In one patient, the nonfunctional cyst was represented as a cervical and upper mediastinal mass with a maximal diameter of 10 cm. Conclusion. Although PCs represent about 0.5% of all changes in the parathyroid glands, they can be suspected preoperatively, especially if a water-like liquid is obtained by a fine needle aspiration biopsy. In order to remove the PC completely without making a lesion on the capsule, with the aim of avoiding parathyreomatosis, but to preserve the recurrent laryngeal nerves, the operation should be performed by an experienced endocrine surgeon.